2011
DOI: 10.1128/iai.01145-10
|View full text |Cite
|
Sign up to set email alerts
|

The Poly-γ- d -Glutamic Acid Capsule of Bacillus anthracis Enhances Lethal Toxin Activity

Abstract: The poly-␥-D-glutamic acid (PGA) capsule is one of the major virulence factors of Bacillus anthracis, which causes a highly lethal infectious disease. The PGA capsule disguises B. anthracis from immune surveillance and allows its unimpeded growth in the host. The PGA capsule recently was reported to be associated with lethal toxin (LT) in the blood of experimentally infected animals (M. H. Cho, et al., Infect. Immun. 78:387-392, 2010). The effect of PGA, either alone or in combination with LT, on macrophages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…The γ-DPGA was filtered, lyophilized, dissolved in water, adjusted to pH 7.4, and stored at −80°C. Fifteen-to 50 kDa-fragments of γ-DPGA were produced by CapD- (25) or HCl-catalyzed hydrolysis (29). Synthetic HPLC-purified γ-DPGA 2-mer and 10-mer were obtained from Bachem and Biopeptide, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The γ-DPGA was filtered, lyophilized, dissolved in water, adjusted to pH 7.4, and stored at −80°C. Fifteen-to 50 kDa-fragments of γ-DPGA were produced by CapD- (25) or HCl-catalyzed hydrolysis (29). Synthetic HPLC-purified γ-DPGA 2-mer and 10-mer were obtained from Bachem and Biopeptide, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A recent report revealed that γ-DPGA and lethal toxin may interact (27). Also, 10-50-kDa fragments of γ-DPGA were reported to enhance LT-mediated killing of J774A.1 cells (29). Whereas the PA monomer, LF, and EF can bind to capsule, the PA prechannel oligomer binds most avidly to the capsule in the nanomolar range.…”
Section: D2-d4 Interface Senses Capsule and Protons During Channelmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we maximized the production of the D-glutamate capsule by B. licheniformis using E medium. The PGA from B. licheniformis, which is a nonpathogenic bacterium treated in a biosafety level 1 facility, has been used as a surrogate for PGA from B. anthracis in several studies, including ours (13,27,46,47). In addition, it has been known that B. anthracis PGA capsule was first polymerized on the cell surface to the high-molecular-mass form (Ͼ100 kDa) and then degraded by capsule depolymerase to the lower-molecular-mass capsule, concomitantly releasing from the cell surface (48).…”
Section: Discussionmentioning
confidence: 99%
“…PGA capsule released from B. anthracis is associated with lethal toxin (LT) in experimental infection models (12). PGA enhances LT-mediated macrophage death (13), indicating that PGA can intensify the LT-induced toxemia that occurs at the terminal stage of anthrax infection.…”
mentioning
confidence: 99%